Concentrated growth factors as a graft material for endoscopic revision tympanoplasty - Nan Zeng; Qiong Yang; Lue Zhang; Jing Hu; Yubo Jin; Shuyi Hong; Shang Yan (Scientific Reports)
Abstract This study aims to evaluate the clinical efficacy of concentrated growth factors (CGF) as a graft material in endoscopic revision tympanoplasty for tympanic membrane perforation. A retrospective analysis was conducted on 30 cases of endoscopic revision tympanoplasty performed at the Otolaryngology Department of Shenzhen Nanshan People’s Hospital between January 1, 2019, and December 31, 2023. Fifteen patients were assigned to the experimental group, in which CGF was used for perforation repair, while the control group (n = 15) received cartilage and perichondrium grafts. Surgical outcomes (intraoperative blood loss, operative time), complications (taste disturbance, ear numbness, postoperative pain, ear fullness, incision infection, etc.), postoperative hearing improvement, and follow-up results (tympanic membrane healing time and healing rate) were statistically analyzed between the two groups. Tympanic membrane perforations in both groups achieved complete healing during follow-up. The experimental group exhibited significantly reduced intraoperative blood loss (15.2 ± 3.8 mL vs. 28.6 ± 5.2 mL; P = 0.003), shorter operative time (52.4 ± 10.1 min vs. 78.9 ± 12.6 min, P = 0.001), lower postoperative complication rates (0% vs. 26.7%; P = 0.021), and accelerated tympanic membrane healing time (14.5 ± 2.3 days vs. 21.8 ± 3.7 days; P < 0.001) compared to the control group. However, no significant differences were observed in postoperative hearing outcomes (air-bone gap closure: 12.1 ± 3.5 dB vs. 13.4 ± 4.1 dB; P = 0.32) or tympanic membrane healing rates (93.3% vs. 86.7%, P = 0.48). Concentrated growth factors are effective and safe as a graft material in endoscopic revision tympanoplasty. CGF is readily available, minimally invasive, and particularly advantageous for use in endoscopic revision tympanoplasty.